(untitled) (Medical Forum Monthly, 2026)
Objective: This study aims to evaluate the frequency of gallbladder perforation and gallstone spillage during LC and assess their impact on postoperative complications and recovery. Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of General Surgery, PAF Hospital, Islamabad from 19th July 2025 to 19th October 2025. Methods: A total of 177 patients undergoing LC were enrolled using stratified random sampling. Data on patient demographics, gallbladder size, number of stones, and surgical outcomes were collected. Descriptive statistics were used to summarize continuous variables such as age, BMI, duration of surgery, and length of hospital stay, presented as mean ± standard deviation or median (interquartile range) depending on the data distribution. Categorical variables, such as gender, presence of gallbladder perforation, gallstone spillage, and postoperative complications, were presented as frequencies and percentages. Results: Gallbladder perforation occurred in 14 (7.9%) patients, while gallstone spillage was observed in 18 (10.2%) patients. Patients with gallstone spillage had comparatively higher rates of postoperative complications, including port-site infection (44.4%), intra-abdominal abscess (27.8%), and reoperation (27.8%). The mean length of hospital stay for the spillage group was 5.2 ± 2.1 days, comparatively longer than the 3.4 ± 1.2 days for the no- spillage group. Conclusion: Gallbladder perforation and gallstone spillage, though infrequent, are associated with significantly worse postoperative outcomes, including higher complication rates, longer hospital stays, and increased surgery durations.